2014
DOI: 10.1074/mcp.m113.034751
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stress Affects the Activity of Metabolic and Growth Factor Signaling Networks and Induces Autophagy Markers in MCF7 Breast Cancer Cells

Abstract: Phosphoproteomic techniques are contributing to our understanding of how signaling pathways interact and regulate biological processes. This technology is also being used to characterize how signaling networks are remodeled during disease progression and to identify biomarkers of signaling pathway activity and of responses to cancer therapy. A potential caveat in these studies is that phosphorylation is a very dynamic modification that can substantially change during the course of an experiment or the retrieva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 72 publications
1
26
0
1
Order By: Relevance
“…However, previous studies have demonstrated that autophagy occurs in most tissues under both physiological and pathological conditions (Shintani and Klionsky, 2004;Levine and Yuan, 2005;Levine and Kroemer, 2008). Autophagy can be dramatically induced and up-regulated by unfavorable stimulus, such as hypoxia and nutrient depletion (Casado et al, 2014). Previous study demonstrated that excessive autophagy may reversely lead to programmed cell death (Shi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have demonstrated that autophagy occurs in most tissues under both physiological and pathological conditions (Shintani and Klionsky, 2004;Levine and Yuan, 2005;Levine and Kroemer, 2008). Autophagy can be dramatically induced and up-regulated by unfavorable stimulus, such as hypoxia and nutrient depletion (Casado et al, 2014). Previous study demonstrated that excessive autophagy may reversely lead to programmed cell death (Shi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Though autophagy plays an essential role in maintaining homeostasis or normal function in basic catabolic mechanism, it also can be dramatically induced and upregulated by unfavorable stimulus, such as hypoxia [34,35]. Therefore, autophagy, a paradox that protects and damages cell survival, depends on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…TFA and phospho-enriched using a TiO 2 based method (Casado et al, 2014). Briefly, eluents were adjusted to 1 mL with 1 M glycolic acid solution and were then incubated with 25 mg of TiO 2 (50% slurry in 1% TFA) for 5 min at room temperature.…”
Section: Liquid Chromatography-tandem Mass Spectrometry (Lc-ms/ms) Anmentioning
confidence: 99%